General Space-Confined On-Substrate Fabrication of Thickness-Adjustable Hybrid Perovskite Single-Crystalline Thin Films - Chen, Yao-Xuan; Ge, Qian-Qing; Shi, Yang; Liu, Jie; Xue, Ding-Jiang; Ma, Jing-Yuan; Ding, Jie; Yan, Hui-Juan; Hu, Jin-Song; Wan, Li-Jun (Journal of the American Chemical Society, 2016)
Organic–inorganic hybrid perovskite single-crystalline thin films (SCTFs) are promising for enhancing photoelectric device performance due to high carrier mobility, long diffusion length, and carrier lifetime. However, bulk perovskite single crystals available today are not suitable for practical device application due to the unfavorable thickness. Herein, we report a facile space-confined solution-processed strategy to on-substrate grow various hybrid perovskite SCTFs in a size of submillimeter with adjustable thicknesses from nano- to micrometers. These SCTFs exhibit photoelectric properties comparable to bulk single crystals with low defect density and good air stability. The clear thickness-dependent colors allow fast visual selection of SCTFs with a suitable thickness for specific device application. The present substrate-independent growth of perovskite SCTFs opens up opportunities for on-chip fabrication of diverse high-performance devices.